Metaphors in Nadin Amizah's Song Lyrics from the Album Untuk Dunia, Cinta dan Kotornya: A Cognitive Semantic Study - Jihan Febrianti Mokoginta; Dakia N. Djou; Nuramila (Raja Zulkarnain Education Foundation, 2026)
This study examines metaphors in Nadin Amizah's song lyrics from the album